Evaluation of Water Diffusion Mechanism on Mechanical Properties of Polypropylene Composites - Oluwayomi Peter Balogun; Adeolu Adesoji Adediran; Joseph Ajibade Omotoyinbo; Kenneth Kanayo Alaneme; Isiaka Oluwole Oladele (International Journal of Polymer Science)
This study evaluates the water diffusion mechanism on mechanical properties of polypropylene reinforced composites. Compounding of the composites into sheets was carried out using the compression moulding techniques by incorporating varying weight percentage of fibers and polypropylene. Mechanical properties of the composites were assessed according to ASTM standards, while the composite fracture surface was examined using a scanning electron microscope. The water absorption behaviour and diffusion mechanisms on mechanical properties of fabricated composites were analysed using a water immersion test and the Fickian diffusion model. The results show that mechanical properties of all polypropylene reinforced composites under dry condition was higher than wet condition. The composites reinforced with 7 wt.% (KOH and NaOH) fibers follow a consistent trend and gave the highest tensile strength and tensile modulus in comparison with pure PP (polypropylene). Addition of fibers into the polypropylene matrix gradually decreases composites impact strength with exception to 3 wt.% and 5 wt.% composites. The hardness properties of reinforced composites were steadily increased as the fiber loading increases which signify strong fiber-matrix bonding. The percentage of water absorbed for all reinforced composites increased as the fiber weight increases and slowly flattened off after 10 days of saturation. The morphological study revealed fiber pullout and delamination of reinforced composites attributed to poor fiber-matrix adhesion amount to water intake. The diffusion transport mechanism of polypropylene composites was observed to obey the Fickian diffusion model.